2017
DOI: 10.1007/s13679-017-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevention for Individuals with Spina Bifida

Abstract: Specific variables related to obesity and spina bifida include individual factors (i.e., body composition and measurement issues, energy needs, eating patterns, physical activity, and sedentary activity) family factors (i.e., parenting/family, peers), community factors (i.e., culture, built environment, healthcare and healthcare providers, and school), and societal factors (i.e., policy issues). Due to the complex etiology of obesity and its increased prevalence in individuals with spina bifida, it is critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 85 publications
0
28
0
3
Order By: Relevance
“…8 In turn, a correlation was established between absolute LM by impedance analysis and arm circumference and skinfold equations, so both measurements would be adequate to assess body composition alterations in these patients. Grogan et al 25 found 50% less LM in children with myelomeningocele compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In turn, a correlation was established between absolute LM by impedance analysis and arm circumference and skinfold equations, so both measurements would be adequate to assess body composition alterations in these patients. Grogan et al 25 found 50% less LM in children with myelomeningocele compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity may lead to worsening of comorbidities, such as restricted ability to move about, pressure ulcers, and a lower level of autonomy, compromising the quality of life, 6 and metabolic consequences, such as insulin resistance (IR), carbohydrate i n t o l e r a n c e , d i a b e t e s m e l l i t u s , fatty liver, dyslipidemia, arterial hypertension (HTN), obstructive sleep apnea syndrome, and increased cardiovascular risk, among others. 7,8 B e c a u s e o f t h e o r t h o p e d i c pathology described above, it is difficult to make accurate measures …”
Section: Introductionmentioning
confidence: 99%
“…Todos aceptaron participar. La edad media fue de 8,1 años (0, [7][8][9][10][11][12][13][14][15][16][17][18]6 20,5 ± 8,9, respectivamente). También se encontró alta correlación (r 2 0,81) entre MM absoluta por impedanciometría y la calculada con perímetro braquial y pliegues cutáneos (20,1 ± 11,5 vs. 17,2 ± 4,9, respectivamente).…”
Section: Resultsunclassified
“…8 A su vez, se encontró correlación entre MM absoluta con impedanciometría y fórmula por perímetro braquial y pliegues cutáneos, por lo que ambas serían medidas apropiadas para evaluar la alteración de la composición corporal en estos pacientes. Grogan et al 25 encontraron 50% menos de MM en niños con mielomeningocele vs. controles.…”
Section: Discussionunclassified
See 1 more Smart Citation